2022
DOI: 10.1002/anie.202200753
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetry‐Based Kinematic Theory for Nanocrystal Morphology Design

Abstract: The growth of crystalline nanoparticles (NPs) generally involves three processes: nucleation, growth, and shape evolution. Among them, the shape evolution is less understood, despite the importance of morphology for NP properties. Here, we propose a symmetrybased kinematic theory (SBKT) based on classical growth theories to illustrate the process. Based on the crystal lattice, nucleus (or seed) symmetry, and the preferential growth directions under the experimental conditions, the SBKT can illustrate the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…66 A recently developed symmetry-based kinematic theory proposed by Ni et al explains well the shape evolution of nanocrystal growth via a surface nucleation process and layer advancement. 67 This theory, reconciling the gap between thermodynamic and kinetic controlled growth, explains well the observed shape evolutions. 67…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…66 A recently developed symmetry-based kinematic theory proposed by Ni et al explains well the shape evolution of nanocrystal growth via a surface nucleation process and layer advancement. 67 This theory, reconciling the gap between thermodynamic and kinetic controlled growth, explains well the observed shape evolutions. 67…”
Section: Resultsmentioning
confidence: 52%
“…67 This theory, reconciling the gap between thermodynamic and kinetic controlled growth, explains well the observed shape evolutions. 67…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, variation of the ratio between DMF and H 2 O led to a change in the final product morphology (Table S4 and Figure S14, Supporting Information), attributed to the changes in solution viscosity, thereby affecting the formation rate of the primary NPs. [12,43,44] The observed changes in the product morphology when using different precursor salts (Table S5 and Figure S15, Supporting Information) mainly result from the different assembly behaviors of the generated NPs due to the distinct reduction property of the precursor. [45,46] In addition, it was found that in the above cases, once there was the presence of CH 3 COOH, the obtained product was a regular assembly structure, proving that CH 3 COOH plays a pivotal role in directional assembly, consistent with the previous report.…”
Section: Formation Mechanism Of Sn/cuo MCmentioning
confidence: 99%